Optimizing the Development of a PLTMH System Using Pelton Turbine Technology to Enhance Energy Efficiency in Remote Areas as an Affordable and Sustainable Renewable Energy Solution - Nur, Ichlas; Effiandi, Nota; Hafiz, Rahmat; Nofriadi; Latif, Abdul (IJIMCE : International Journal of Innovation in Mechanical Construction and Energy, 2025)
Remote areas often face challenges in providing reliable and affordable access to electricity, In West Sumatra, there are still many 3T areas that lack access to electricity. Renewable energy sources, such as Micro Hydro Power Plants (PLTMH), can be the ideal solution to meet the energy needs in these areas. However, to enhance the efficiency and sustainability of PLTMH, it is essential to optimize the development and utilization of technology, particularly in the application of Pelton turbines.The goal of this research is to produce a micro-hydro power plant that can work optimally and efficiently to generate electrical energy for people without access to electricity. It is hoped that this research can also help improve the community's economic situation by meeting their economic needs. This activity aligns with the goals outlined in the PNP strategic plan, which focuses on developing technology to support the community's economy.The method used in this research is applicable design and construction based on community needs, followed by tool design, tool making, assembly.Initial design data is discharge 50 Lt/s, Head 25 m. From the calculation results, it is found that the absolute speed of the jet is 21.6 m/s, the optimal jet diameter is 2.9 mm, the diameter of the puncture circle is 132.4 mm, the number of bowls is 34, the width of the bowl is 8.26 mm, the height of the bowl is 6, .96 mm, Bowl Depth 2.61 mm, Bowl Mold Allowance 11.92 mm, and generator 3 kW. The process of making a Pelton turbine involves making the Pelton turbine runner, installing the turbine blade to the runner, making the nozzle, installing the generator, painting the tool.